Iatrogenic pseudoaneurysm of the lateral femoral circumflex artery following antegrade intramedullary femur nailing: a case report - Khirul Ashar, Nur Ayuni; Ismail, Imma Isniza; Lingam, Rahul (Springer Science and Business Media LLC, 2024)
Few cases of femoral artery pseudoaneurysm or its branches have been reported following intramedullary nailing of femur fractures. The occurrence of a false aneurysm of the lateral femoral circumflex artery (LFCA) for such a fracture has never been reported so far. We report a case of a young male with a delayed presentation of right thigh swelling following an antegrade interlocking nail femur. Ultrasonography and CT angiography of the right thigh confirmed a pseudoaneurysm communicating with LFCA. After unsuccessful ultrasound-guided compression therapy, the patient underwent embolization of the right LFCA pseudoaneurysm by an interventional radiologist. Although intramedullary nailing is considered a safe procedure, a pseudoaneurysm should be suspected when the patient presents with a painful swelling after the surgery. Glue embolization of the artery should be considered as one of the treatment options, as it yields favorable outcomes with less morbidity.